BIBLIOMETRIC ANALYSIS OF WOMEN'S PARTICIPATION IN MUSRENBANG: TRENDS, INNOVATIONS, AND CHALLENGES INREGIONAL DEVELOPMENT PLANNING - Wahyul AZ; Rosdiana (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal